Preparation process of low-bleeding concrete with graded utilization of machine-made sand and stone powder
By classifying and utilizing manufactured sand and gravel powder and feeding it in stages, the problem of not being able to balance anti-bleeding performance and workability caused by the difference in the particle size characteristics of stone powder in concrete has been solved, realizing the preparation of low-bleeding concrete and improving construction fluidity and pumpability.
Patent Information
- Application Number
- CN202611264781.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies cannot effectively utilize the different particle size characteristics of manufactured sand and gravel, resulting in a difficulty in achieving both the anti-bleeding performance and workability of concrete. In particular, when the stone powder content is low, the paste's encapsulation and water retention capacity decrease, and when the stone powder content increases, the viscosity increases, affecting the flowability.
The stone powder generated during the production of manufactured sand is classified into F1 ultrafine water-control grade, F2 slurry-filling grade, and F3 micro-aggregate grade. Through staged feeding and pre-preparation of ultrafine water-control slurry, the powder participates in water control, slurry filling, and micro-aggregate gradation construction, respectively, to form a clear granular structure.
It achieves a coordinated improvement in the low bleeding performance and flowability of concrete, reduces pressure bleeding rate and plastic viscosity index, and ensures the stability of construction flowability and pumpability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of building materials and concrete, and in particular to a preparation process for low-bleeding concrete using graded utilization of manufactured sand and gravel powder. Background Technology
[0002] With the limitation of natural sand resources and the development of green building materials, manufactured sand has gradually become an important source of fine aggregate in concrete production. Manufactured sand is typically produced by crushing, shaping, and screening rocks, and a certain amount of stone powder with a particle size less than 0.075 mm is generated during the production process. The rational utilization of manufactured sand and stone powder can improve the utilization rate of mineral resources, reduce solid waste emissions, and improve the fine particle composition of concrete.
[0003] However, the particle size distribution, morphology, and surface properties of manufactured sand and gravel powder differ from those of fine particles in natural sand. When the stone powder content is low, insufficient fine particle filling in the concrete system leads to decreased paste encapsulation and water retention capacity, easily causing aggregate settling and bleeding. When directly increasing the stone powder content to improve water retention, the increased specific surface area due to the presence of more fine particles enhances the adsorption of water and admixture components, increasing the viscosity of the concrete paste, decreasing its flowability, and potentially increasing resistance during mixing and pumping. Therefore, in the resource utilization of manufactured sand and gravel powder, how to improve the anti-bleeding performance of concrete while avoiding a decrease in workability due to increased fine powder becomes a problem that needs to be solved.
[0004] In existing technologies, concrete performance is typically improved by controlling the content of manufactured sand and gravel powder, optimizing the fine aggregate gradation, or adding auxiliary powder materials. For example, Chinese patent CN117447142A discloses a low-gravel manufactured sand low-bleeding concrete and its preparation method. This technology improves the water retention and anti-segregation properties of low-gravel manufactured sand concrete by introducing auxiliary powder materials and combining them with a specific admixture system. This method can reduce concrete bleeding to a certain extent, but it mainly addresses the paste stability problem caused by insufficient gravel powder content. It lacks further control over the differences in the role of gravel powder of different particle sizes in the concrete system and the spatial distribution of gravel powder particles.
[0005] Chinese patent CN103113033B discloses a method for improving the performance of manufactured sand concrete, which improves the workability of concrete by adjusting the particle size distribution of manufactured sand and increasing the fine particle component. This method mainly achieves performance improvement through overall gradation optimization, but it lacks specific control over the functional differences between different particle sizes of stone powder formed during the manufactured sand production process, and the location of action of different particle sizes of stone powder after entering the concrete system.
[0006] Furthermore, current methods of utilizing stone powder in manufactured sand concrete typically involve adding stone powder smaller than 0.075 mm as a whole, adjusting the composition solely based on indicators such as total stone powder content, specific surface area, or average particle size. Since stone powder particles within different particle size ranges have different roles in water migration, paste filling, particle packing, and admixture adsorption, adding undifferentiated stone powder as a whole to the concrete system can easily lead to problems such as some fine particles excessively adsorbing admixtures, while some coarse particles fail to effectively improve the fine aggregate gradation. This makes it difficult to simultaneously achieve the desired balance between reducing bleeding performance and maintaining concrete flowability.
[0007] Therefore, in view of the complex particle size composition of manufactured sand and gravel powder and the significant differences in the effects of different particle sizes, there is still a need for a technical solution that can fully utilize the characteristics of stone powder of different particle sizes and achieve coordinated improvement of concrete's anti-bleeding performance and workability. Summary of the Invention
[0008] The purpose of this invention is to overcome the above-mentioned problems existing in the prior art and to provide a preparation process for low-bleeding concrete using graded and utilized manufactured sand and gravel powder. By functionalizing and grading the same rock-derived stone powder, and combining it with the prefabrication and staged feeding of ultrafine water-control slurry, different particle sizes of stone powder can participate in water control, slurry filling and micro-aggregate gradation construction respectively.
[0009] The present invention provides a process for preparing low-bleeding concrete using graded and utilized manufactured sand and gravel powder, comprising the following steps: S1. The same rock-derived fine stone powder raw material generated during the production of manufactured sand and obtained through dust collection or fine material collection is classified to obtain F1 ultrafine water-controlled stone powder, F2 slurry-filled stone powder and F3 micro-aggregate stone powder; wherein, the D50 of the F1 ultrafine water-controlled stone powder is 1.5-5.0 μm and the D90 is not greater than 8 μm, the D10 of the F2 slurry-filled stone powder is not less than 5 μm, the D50 is 10-22 μm and the D90 is not greater than 35 μm, the D10 of the F3 micro-aggregate stone powder is not less than 25 μm, the D50 is 40-70 μm and the D90 is not greater than 100 μm, and the dry mass ratio of the F1 ultrafine water-controlled stone powder, the F2 slurry-filled stone powder and the F3 micro-aggregate stone powder is 1∶(2-6)∶(3-9); S2. Add the dispersant to the first portion of water, add the F1 ultrafine water-controlling stone powder under stirring conditions of 1000-2000 r / min and disperse for 3-10 min, then perform surface occupancy treatment for 5-20 min, then add the amphoteric water-controlling polymer under stirring conditions of 300-600 r / min and stir for 2-5 min, and mature for 10-30 min to obtain the F1 ultrafine water-controlling slurry; wherein, the amount of dispersant added, based on the effective solid mass of the dispersant corresponding to the unit mass of F1 ultrafine water-controlling stone powder, is 65%-85% of the saturated adsorption capacity Qs of the F1 ultrafine water-controlling stone powder for the dispersant; the saturated adsorption capacity Qs is the adsorption plateau value determined after preparing a dispersion system of F1 ultrafine water-controlling stone powder and deionized water at a mass ratio of 1:1 at 24-26℃, adding the dispersant and equilibrating for 30 min; S3. Add the manufactured sand, the F3 micro-aggregate grade stone powder and coarse aggregate into the mixer and dry mix for 20-40 seconds to distribute the F3 micro-aggregate grade stone powder between the manufactured sand particles. S4. Add cement, mineral admixtures and the F2 slurry filler stone powder, and dry mix for 15-30 seconds; S5. Add 65% to 85% of the total mixing water mass of the concrete and 70% to 90% of the total amount of the main polycarboxylate superplasticizer, and wet mix for 40 to 70 seconds to form a preliminarily dispersed main slurry of cement, mineral admixtures and F2 slurry filler stone powder. S6. Add the F1 ultrafine water-controlling slurry, the remaining mixing water and the remaining main polycarboxylate superplasticizer, and stir for 30-60 s to obtain the low-bleeding concrete; wherein, the water used to prepare the F1 ultrafine water-controlling slurry is included in the total mixing water of the concrete.
[0010] After the same source fine stone powder raw material is divided into three functional particle sizes, F1, F2, and F3, F3 first enters the manufactured sand and coarse aggregate system, participating in the adjustment of the fine-end particle size distribution of the manufactured sand and reducing the large-scale voids between aggregate particles. F2 then forms a fully filled main slurry together with cementitious materials. F1 first completes part of the surface occupancy with a dispersant of 65%–85% Qs, and then forms reversible particle association with amphoteric water-controlling polymers, and is added at the end in the form of an independent water-controlling slurry. As a result, the main slurry first establishes a uniform coating and dispersion state, and the F1 ultrafine water-controlling slurry then forms a shear-reversible dynamic constraint on free water, so that the proportion of ordinary bleeding and pressurized drainage is reduced simultaneously compared with the comparison of not using the above-mentioned graded utilization and water-controlling slurry treatment. At the same time, the associated structure can be partially dissociated under strong shear, avoiding excessive increase in plastic viscosity index, thereby taking into account slump retention, pump-related rheological properties, and 28-day compressive strength.
[0011] Preferably, the F1 ultrafine water-controlled stone powder, F2 slurry-filled stone powder, and F3 micro-aggregate stone powder are obtained by dynamic air classification, cyclone classification, or wet classification, and the particle size distribution overlap coefficient of F1 and F2, and F2 and F3, does not exceed 20%.
[0012] By employing the above-described grading method and limiting the overlap coefficient of particle size distribution between adjacent particle sizes, clear particle size boundaries can be maintained among the three particle sizes, while retaining appropriate particle size transitions. Thus, the surface effect of ultrafine particles (F1), the slurry-scale filling effect (F2), and the micro-aggregate skeleton effect (F3) can each play their respective roles, forming a coordinated synergy in the continuous particle size transition, making the stone powder grading results identifiable and batch-to-batch reproducible.
[0013] Preferably, the proportion of particles with a diameter of less than 2 μm in the F1 ultrafine water-controlled stone powder is not higher than 40% of the mass of the F1 ultrafine water-controlled stone powder; the D50 of the F2 slurry-filled stone powder is 0.5 to 1.2 times the D50 of the cement used, and the D50 of the F3 micro-aggregate stone powder is 2.0 to 6.0 times the D50 of the cement used.
[0014] Limiting the proportion of particles smaller than 2 μm in F1 to the specified range ensures that the ultrafine particles have sufficient surface interaction sites and that their overall specific surface area is within a range conducive to dispersion and water control. F2, with a scale close to that of cement particles, enters the pores and interparticle spaces of the paste, while F3, with a particle size several times that of cement D50, participates in the fine aggregate gradation. This allows the three types of stone powder to establish a clear dimensional relationship around the cement particle size, thereby forming a layered and continuous particle packing.
[0015] Preferably, in each cubic meter of the low-bleeding concrete, the amount of F1 ultrafine water-controlling grade stone powder is 3-15 kg, the amount of F2 paste-filled grade stone powder is 15-50 kg, the amount of F3 micro-aggregate grade stone powder is 20-70 kg, and the total amount of the three is 45-120 kg; the dry weight ratio of F1 ultrafine water-controlling grade stone powder, F2 paste-filled grade stone powder and F3 micro-aggregate grade stone powder is 1:(3-5):(4-7).
[0016] The unit volume dosage and dry mass ratio configure the interface water control function of F1, the slurry filling function of F2, and the fine-end particle gradation adjustment function of F3 within the same mix proportion framework. F1 is kept at a low but effective addition amount, while F2 and F3 undertake the slurry filling and composite fine aggregate construction in an increasing proportion, so that the total amount of the three-stage stone powder matches their respective functions, which is conducive to the formation of a uniform slurry and continuous particle structure under the condition of a given mixing water volume.
[0017] Preferably, based on 100 parts by weight of the F1 ultrafine water-controlling grade stone powder, the F1 ultrafine water-controlling slurry comprises the following components: 100 parts by weight of F1 ultrafine water-controlling grade stone powder; 67-130 parts by weight of water; 0.10-0.80 parts by weight of dispersant; 0.005-0.10 parts by weight of amphoteric water-controlling polymer; and 0-0.10 parts by weight of defoamer; the solid content of the F1 ultrafine water-controlling slurry is 43%-60%.
[0018] By defining the proportions of water, dispersant, amphoteric water-controlling polymer, and optional defoamer based on F1 mass, and controlling the solid content between 43% and 60%, ultrafine stone powder can obtain dispersion space in a continuous aqueous phase while maintaining a sufficient solid concentration to carry the water-controlling structure. The dispersant is used to establish particle surface occupancy, the amphoteric water-controlling polymer subsequently forms dynamic constraints, and the defoamer adjusts the bubble state in the slurry as needed, making the resulting water-controlling slurry easy to meter, transport, and incorporate at the end.
[0019] Preferably, the dispersant is selected from polyether phosphate, polycarboxylic acid dispersants with a carboxyl density of 0.40-0.50 mmol / g, and combinations thereof; the amphoteric water-controlling polymer is a water-soluble copolymer containing both anionic and cationic structural units, wherein the anionic structural unit includes 2-acrylamido-2-methylpropanesulfonic acid structural units, and the cationic structural unit includes dimethyldiallylammonium chloride structural units.
[0020] Polyether phosphates, polycarboxylic acid dispersants, or combinations thereof, can form controlled sites on the surface of F1 particles, preserving space for subsequent amphoteric hydrophilic polymers to participate in interfacial interactions. Water-soluble copolymers containing sulfonic acid anionic structural units and quaternary ammonium cationic structural units can interact with the aqueous phase and particle interface through hydrophilic segments and positive and negatively charged structures to form a shear-dependent particle association and water-constrained network.
[0021] Preferably, the relative weight-average molecular weight of the amphoteric water-controlling polymer is 200,000 to 2,000,000, and the cationic structural unit accounts for 5 to 20 mol% of all structural units of the amphoteric water-controlling polymer; based on 100 parts by mass of the F1 ultrafine water-controlling grade stone powder, the amount of the dispersant is 0.20 to 0.50 parts by mass, and the amount of the amphoteric water-controlling polymer is 0.015 to 0.060 parts by mass.
[0022] The relative weight-average molecular weight provides the scale for polymer segments to act across multiple hydrated particle spacings, while 5–20 mol% of cationic structural units gives the segments a suitable interfacial binding capacity. By controlling the dosage of dispersant and amphoteric water-controlling polymer, a balance can be established between particle pre-dispersion, segmental association, and shear response, allowing the F1 ultrafine water-controlling slurry to form a certain structure when stationary and to disperse smoothly and integrate into the bulk slurry during stirring.
[0023] Preferably, the saturated adsorption capacity Qs is determined as follows: At 24–26°C, different initial amounts of the dispersant are added to a dispersion system composed of 50.00 g of F1 ultrafine water-controlled stone powder and 50.00 g of deionized water, mixed and equilibrated for 30 min, and the resulting dispersion system is subjected to solid-liquid separation. The concentration of the dispersant in the supernatant is measured. The amount of unadsorbed dispersed powder is calculated based on the concentration of the dispersant in the equilibrium liquid phase and the total amount of liquid in the equilibrium system. The adsorption capacity per unit mass of F1 ultrafine water-controlled stone powder is calculated based on the difference between the initial amount of dispersant added and the amount of unadsorbed dispersed powder. The adsorption plateau value when the adsorption capacity no longer increases significantly with the increase of the initial amount of dispersant added is determined as the saturated adsorption capacity Qs.
[0024] By varying the initial amount of dispersant added under the same conditions of 50.00 g stone powder, 50.00 g deionized water, temperature, and equilibration time, and then calculating the adsorption capacity per unit mass of F1 by back-calculating the dispersant concentration in the equilibrium liquid phase and the total amount of liquid in the equilibrium system, the actual surface state of the stone powder can be transformed into a measurable adsorption curve. Using the plateau value of the curve as Qs, a dosage benchmark corresponding to the surface adsorption capacity of different batches of F1 can be determined, providing a unified comparison benchmark, measurement path, and verifiability for surface occupancy control of 65%–85% Qs.
[0025] Preferably, the apparent viscosity of the F1 ultrafine water-controlled slurry at 25°C and a shear rate of 50 s⁻¹ is 50–500 mPa·s; after shearing at 500 s⁻¹ for 60 s, its apparent viscosity decreases by 30%–65% compared to before shearing; after stopping the 500 s⁻¹ shearing and allowing it to stand for 5 min, it is sheared at 50 s⁻¹ for 10 s, and the apparent viscosity at the 10th s is taken as the recovered apparent viscosity; the apparent viscosity recovery rate is the ratio of the recovered apparent viscosity to the apparent viscosity at the 60th s after shearing at 50 s⁻¹ for 60 s, and the apparent viscosity recovery rate is 35%–75%.
[0026] The initial apparent viscosity, the viscosity decrease after strong shearing, and the recovery rate after static settling collectively define the shear reversible response of the F1 ultrafine water-controlled slurry. Under high shear, the slurry's viscosity decreases, facilitating its diffusion and mixing with the main slurry during final mixing. After the strong shearing stops, some structures recover within a specified time, allowing for the re-establishment of dynamic constraints on the aqueous phase and fine particles, ensuring that construction flow and static water control follow the same rheological path.
[0027] Preferably, each cubic meter of the low-bleeding concrete comprises 240–380 kg of cement, 30–100 kg of fly ash, 30–120 kg of mineral powder, 3–15 kg of F1 ultrafine water-controlling grade stone powder, 15–50 kg of F2 slurry-filling grade stone powder, 20–70 kg of F3 micro-aggregate grade stone powder, 650–900 kg of manufactured sand, 900–1150 kg of coarse aggregate, 140–175 kg of water, and 3–10 kg of polycarboxylate admixture; in the combined fine aggregate composed of manufactured sand and F3 micro-aggregate grade stone powder, particles with a diameter of 0.075–0.15 mm account for 3.0%–6.5% of the mass of the combined fine aggregate, and the fineness modulus of the combined fine aggregate is 2.5–3.1.
[0028] The unit volume range of the cement, fly ash, mineral powder, graded stone powder, aggregate, water, and polycarboxylate admixture provides a complete concrete mix design system for the functional allocation of graded stone powder. F3 participates in the adjustment of the fine-end particle size distribution of manufactured sand, fills the fine particle range, and reduces large-scale voids between aggregate particles; the main cementitious material, F2 filler particles, and F1 water-controlling slurry are sequentially combined to form a mixed structure in which the skeleton, slurry, and moisture state are coordinated.
[0029] The present invention, by adopting the above technical solution, has the following beneficial effects: (1) The same source fine stone powder raw material collected during the production of manufactured sand is divided into F1 ultrafine water-control grade, F2 slurry-filling grade and F3 micro-aggregate grade, and the D10, D50, D90 and dry weight ratio of each grade are limited, so that the surface water control, slurry-scale filling and fine-end particle gradation adjustment functions of stone powder have clear division of labor. The three particle sizes are continuously connected along the particle size, which can form a clear layered combination structure between aggregate, cementitious particles and water phase.
[0030] (2) F1 ultrafine stone powder is first contacted with the dispersant under high shear conditions and the surface occupancy treatment is completed. Then, the amphoteric water-controlling polymer is added at a lower rotation speed and matured, so that the pre-dispersion of particles and the association with the polymer are established in sequence. The amount of dispersant added is determined by 65% to 85% of the saturated adsorption capacity Qs, so that the addition benchmark corresponds to the actual surface adsorption capacity of the stone powder, forming a batch-measurable and dosage-verifiable water-controlling slurry preparation process.
[0031] (3) F3 is first dry-mixed with manufactured sand and coarse aggregate, and F2 is then added together with cement and mineral admixtures. The main mixing water and the main polycarboxylate superplasticizer are added in two stages according to the proportion. Finally, F1 ultrafine water-control slurry is introduced. This sequence allows the distribution of micro-aggregates, the initial dispersion of the main slurry, and the final water control to be completed in sequence, reducing the agglomeration of fine powder and the local accumulation of free water, making the concrete mixing state more uniform.
[0032] (4) The solid content, dispersant and amphoteric water-controlling polymer dosage, as well as the polymer molecular weight and cationic structural unit ratio of F1 ultrafine water-controlling slurry are matched to give the slurry the specified initial viscosity, shear thinning range and resting recovery ability. Under high shear, the slurry is easy to diffuse and mix, and after shearing stops, the associated structural parts recover, thereby establishing a continuous water-constraining path between the construction flow process and the resting stage.
[0033] (5) By limiting the unit volume of cement, fly ash, mineral powder, grade III stone powder, manufactured sand, coarse aggregate, water, and polycarboxylate admixture, and by performing quality weighted calculations based on the 0.075–0.15 mm gradation test values of manufactured sand and F3 respectively, the aggregate skeleton, cement paste, and graded stone powder are in a verifiable and coordinated proportion. F3 participates in the fine-end particle gradation adjustment of manufactured sand, which can fill the fine particle range and reduce the large-scale voids between aggregate particles, thereby inhibiting the upward migration of free water and forming stable, repeatable low-bleeding concrete.
[0034] (6) Pressure bleeding rate and concrete rheological tests verified the graded utilization effect from two dimensions: pressure drainage and viscous resistance. In the example, while maintaining slump and a low ordinary bleeding rate, the pressure bleeding rate and plastic viscosity index were significantly reduced compared with the control example that did not adopt the graded utilization and water control slurry treatment of the present invention. This shows that the three-stage stone powder division and the addition of F1 ultrafine water control slurry at the end can take into account both the anti-bleeding and pump-related rheological states. Detailed Implementation
[0035] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0036] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0038] Unless otherwise specified, the conventional raw materials, monomers and reagents used in the following examples are commercially available; the amphoteric water-controlling polymer and polycarboxylic acid dispersant were obtained according to the preparation and characterization methods described below.
[0039] In all embodiments, unless otherwise specified, all percentage contents are mass percentages, and the dosage per cubic meter is based on the volume of the finished concrete. The dosage of dispersant and the saturated adsorption capacity Qs are calculated based on the effective solid mass of the dispersant. The dosage of amphoteric water-controlling polymer is calculated based on the powder mass after vacuum drying to constant weight. The dosage of defoamer and main polycarboxylate superplasticizer is calculated based on the product mass. The solid content of F1 ultrafine water-controlling slurry is calculated by dividing [F1 mass + effective solid mass of dispersant + dry polymer mass + solid mass of defoamer] by the total mass of the slurry and then multiplying by 100%. The total water consumption of concrete includes added water, water in F1 ultrafine water-controlling slurry, and carrier water introduced by liquid admixtures; the added water volume listed in each step has deducted the carrier water introduced by liquid admixtures in the same step.
[0040] The amphoteric water-controlling polymer was prepared using an aqueous free radical copolymerization method. Taking the polymer used in Example 1 as an example, 2-acrylamido-2-methylpropanesulfonic acid and dimethyldiallyl ammonium chloride were dissolved in deionized water at a molar ratio of 88:12, making the total monomer mass fraction 30.0%. After purging with nitrogen for 30 min, the temperature was raised to 50°C, and 0.08% of ammonium persulfate aqueous solution and 0.08% of sodium bisulfite aqueous solution (based on the total monomer mass) were added dropwise over 30 min, and the reaction was maintained at this temperature for 4 h. The pH was adjusted to 7.0 with sodium hydroxide solution, and the polymer was precipitated with ethanol, vacuum dried at 50°C, and pulverized to obtain a powdered water-soluble copolymer. By adjusting the molar ratio of the two monomers to 95:5 to 80:20 and adjusting the total amount of initiator to 0.08% to 0.40% of the total monomer mass, a series of polymers with relative weight-average molecular weights of 200,000 to 2,000,000 and cationic structural units of 5 to 20 mol% were obtained in the examples.
[0041] The relative weight-average molecular weight of the amphoteric water-controlling polymer was determined by aqueous gel permeation chromatography, using 0.10 mol / L sodium nitrate aqueous solution as the mobile phase and polyethylene glycol standard for calibration. The mole fraction of the cationic structural unit was determined by proton nuclear magnetic resonance (NMR) using heavy water as the solvent, calculated based on the integral ratio of the characteristic hydrogen on the dimethyldiallylammonium chloride ring to the characteristic hydrogen of the methyl group of 2-acrylamido-2-methylpropanesulfonic acid. Three samples from each batch were independently analyzed, and the arithmetic mean was taken.
[0042] The polycarboxylic acid dispersant was prepared by free radical copolymerization of methoxy polyethylene glycol methacrylate and an aqueous solution of acrylic acid. The number average molecular weight of the methoxy polyethylene glycol methacrylate was 2400. Example 5 used a monomer molar ratio of 1:1.13, with a total monomer mass fraction of 45.0%. After purging with nitrogen for 30 min, 0.50% ammonium persulfate and 0.20% sodium bisulfite (by mass of total monomer) were added at 65°C. The addition was completed over 2 h, and the mixture was kept at this temperature for 1 h. After cooling, the pH was adjusted to 7.0 with sodium hydroxide solution, and then deionized water was added to adjust the product solid content to 30.0%. Carboxyl density was determined by potentiometric titration: 1.000 g of product (dry basis) was weighed, 100 mL of deionized water and 4.0 g of a pre-converted H-form strong acid cation exchange resin were added, and the mixture was stirred for 30 min to convert the carboxylate to the carboxylic acid form. The resin was removed by filtration, and the resin was washed three times with 10 mL of deionized water each time. The filtrates and washings were combined, and potentiometric titration was performed with 0.1000 mol / L sodium hydroxide standard solution. The carboxyl density was calculated based on the alkali consumption at the equivalence point after subtracting the blank. The number-average molecular weight was determined by the aqueous gel permeation chromatography method described above.
[0043] Examples 1-10 all used 310 kg of cement, 65 kg of fly ash, 75 kg of mineral powder, 1020 kg of coarse aggregate, 160 kg of total water, and 6.40 kg of the main polycarboxylate superplasticizer product. Each group was measured according to the target unit volume mix ratio. When the amounts of F1, F2, and F3 changed, the amount of manufactured sand was adjusted first. The apparent density of stone powder and manufactured sand of different lithologies was measured separately, and the mix ratio was corrected using the absolute volume method. The unit volume yield was verified by the measured apparent density of fresh concrete, and the actual batch weight was converted according to the yield correction factor. The solid content of the main polycarboxylate superplasticizer was 20.0%, and the water in the product was included in the 160 kg of total water.
[0044] Example 1 This embodiment discloses a preparation process for low-bleeding concrete using graded utilization of manufactured sand and gravel powder.
[0045] This embodiment uses fine stone powder from the same limestone source obtained through dust collection and fine material collection in a limestone manufactured sand production line. The cement is P·O 42.5 ordinary Portland cement with a D50 of 18.0 μm; the fly ash is Grade I low-calcium fly ash with a loss on ignition of 2.8%; the mineral powder is S95 grade granulated blast furnace slag powder with a specific surface area of 428 m² / kg. The manufactured sand has a stone powder content of 2.1%, a 0.075–0.15 mm particle content of 3.0%, and an apparent density of 2700 kg / m³; the stone powder content and the 0.075–0.15 mm particle content are different testing indicators. The coarse aggregate is 5–25 mm continuously graded crushed stone. The main polycarboxylate superplasticizer has a solid content of 20.0% and a water reduction rate of 27.0%.
[0046] The dispersant is a powdered polyether phosphate ester with an active ingredient content of 98.0%, a number-average molecular weight of 2800, and a phosphorus content of 1.8%. The amphoteric water-controlling polymer is a powdered water-soluble copolymer obtained by copolymerizing 2-acrylamido-2-methylpropanesulfonic acid and dimethyl diallyl ammonium chloride, precipitated with ethanol, and vacuum dried to constant weight at 50°C; all measurements below are based on the mass of this dried powder. Its relative weight-average molecular weight is 850,000, and the dimethyl diallyl ammonium chloride structural unit accounts for 12 mol% of all structural units. The defoamer is a polyether-modified silicone defoamer with a solid content of 30.0%.
[0047] For every cubic meter of concrete, the following materials are used: 310 kg of cement, 65 kg of fly ash, 75 kg of mineral powder, 8 kg of F1 ultrafine water-control grade stone powder, 32 kg of F2 slurry-filling grade stone powder, 48 kg of F3 micro-aggregate grade stone powder, 760 kg of manufactured sand, 1020 kg of coarse aggregate, 160 kg of total water, and 6.40 kg of main polycarboxylate superplasticizer.
[0048] The specific preparation process steps are as follows: S1. A dynamic air classifier is used to continuously classify the same rock source stone powder. The rotor speed of the classifier is set to 4800 r / min and 2600 r / min respectively, and the feed rate is 1.20 t / h, to obtain F1 ultrafine water-controlled stone powder, F2 slurry-filled stone powder and F3 micro-aggregate stone powder.
[0049] F1 has a D50 of 3.2 μm and a D90 of 6.8 μm, with particles smaller than 2 μm accounting for 28.0%. F2 has a D10 of 7.0 μm, a D50 of 16.0 μm, and a D90 of 30.0 μm. F3 has a D10 of 30.0 μm, a D50 of 55.0 μm, and a D90 of 92.0 μm. The D50 of F2 is 0.89 times that of cement, and the D50 of F3 is 3.06 times that of cement. The dry weight ratio of F1, F2, and F3 is 1:4:6. The particle size distribution overlap coefficient between F1 and F2 is 12.0%, and the overlap coefficient between F2 and F3 is 14.0%.
[0050] S2. Add 8.000 kg of the first portion of water to a pulping container equipped with a high-speed dispersion disc. Add 26.1 g of dispersant product to the first portion of water and stir at 1500 r / min for 60 s. This product contains 25.6 g of effective dispersant solids. Maintaining 1500 r / min, add 8.00 kg of F1 uniformly over 90 s, continue dispersing for 6 min, stop stirring and perform a 12 min surface occupancy treatment. Then stir at 450 r / min, add 3.20 g of dry polymer and 2.40 g of defoamer product, continue stirring for 3 min, and then let stand for 20 min to mature, obtaining the F1 ultrafine water-controlled pulp. Based on 100 parts by weight of F1, the first part is water (100 parts by weight), the effective solids of the dispersant is 0.32 parts by weight, the dry polymer is 0.040 parts by weight, and the defoamer product is 0.030 parts by weight. The solids content of F1 ultrafine water-controlled slurry is 50.1%, calculated by dividing the sum of the masses of F1, the effective solids of the dispersant, the dry polymer, and the solids of the defoamer by the total mass of the slurry.
[0051] According to the saturated adsorption capacity test method described later, the Qs of this batch of F1 for the dispersant is 4.00 mg / g, and the actual effective solid dispersant added is 3.20 mg / g, which is 80.0% of Qs.
[0052] S3. Add 760 kg of manufactured sand, 48 kg of F3, and 1020 kg of coarse aggregate to a twin-shaft forced mixer and dry mix at 32 r / min for 30 s. The content of 0.075–0.15 mm particles in the manufactured sand and F3 is 3.0% and 24.0%, respectively. After weighting by their respective masses, this fraction accounts for 4.2% of the combined fine aggregate, and the fineness modulus is 2.78.
[0053] S4. Add 310 kg of cement, 65 kg of fly ash, 75 kg of mineral powder and 32 kg of F2 to the mixer and dry mix at 32 r / min for 20 s.
[0054] S5. After premixing 115.904 kg of added water and 5.12 kg of the main polycarboxylate superplasticizer product for 30 s, add it to the mixer within 20 s and wet mix at 32 r / min for 55 s. The main polycarboxylate superplasticizer product introduces 4.096 kg of carrier water. The total water entering the system in this step is 120.000 kg, accounting for 75.0% of the total water used; the main polycarboxylate superplasticizer product added in this step accounts for 80.0% of its total usage.
[0055] S6. Add all of the F1 ultrafine water-controlling slurry obtained in S2, 30.974 kg of added water, and the remaining 1.28 kg of the main polycarboxylate superplasticizer product to the mixer sequentially within 20 seconds, and mix at 32 r / min for 45 seconds to obtain low-bleeding concrete. The water in the F1 ultrafine water-controlling slurry, the defoamer carrier water, and the main polycarboxylate superplasticizer carrier water are all included in the total water consumption of 160 kg.
[0056] Example 2 This embodiment discloses a preparation process for low-bleeding concrete using graded utilization of manufactured sand and gravel powder, employing a low-value combination of particle size, total stone powder, slurry preparation time, and segmented feeding ratio.
[0057] In each cubic meter of concrete, the amounts of F1, F2, and F3 are 5 kg, 15 kg, and 25 kg, respectively, and the amount of manufactured sand is 803 kg. The amounts of other materials are the same as in Example 1. The dry weight ratio of F1, F2, and F3 is 1:3:5, and the total amount is 45 kg. The D50 of F1 is 1.5 μm, the D90 is 5.6 μm, and particles smaller than 2 μm account for 40.0%; the D10 of F2 is 5.0 μm, the D50 is 10.0 μm, and the D90 is 24.0 μm; the D10 of F3 is 25.0 μm, the D50 is 40.0 μm, and the D90 is 78.0 μm. The D50 of cement is 20.0 μm, the ratio of F2 to cement D50 is 0.50, and the ratio of F3 to cement D50 is 2.00.
[0058] During pulping, 6.500 kg of water (part 1), 10.2 g of dispersant product, and 0.75 g of dry polymer were added; no defoamer was added. The effective solids of the dispersant were 10.0 g, which is 0.20 parts by weight per 100 parts by weight of F1; the dry polymer was 0.015 parts by weight, and the pulp solids content was 43.5%. The Qs of this batch of F1 were 3.08 mg / g, and the effective solids of the dispersant added were 65.0% of the Qs. F1 was dispersed at 1000 r / min for 3 min, followed by a site-occupancy treatment for 5 min; the dry polymer was stirred at 300 r / min for 2 min and matured for 10 min. The relative weight-average molecular weight of the amphoteric water-controlling polymer was 200,000, and the cationic structural units accounted for 5 mol%.
[0059] S3: Dry mixing for 20 s; S4: Dry mixing for 15 s. S5: Add 100.416 kg of added water and 4.48 kg of the main polycarboxylate superplasticizer product. The water entering the system is 104.000 kg, accounting for 65.0% of the total water. Wet mixing for 40 s. S6: Add all of the F1 ultrafine water-controlled slurry, 47.964 kg of added water, and 1.92 kg of the main polycarboxylate superplasticizer product. Stir for 30 s. The manufactured sand used in this example, along with F1 to F3, all came from the same limestone manufactured sand production line. The content of 0.075–0.15 mm particles in the manufactured sand and F3 were 2.75% and 11.0%, respectively. This fraction accounted for 3.0% of the combined fine aggregate, with a fineness modulus of 2.91. The remaining equipment and operating conditions were the same as in Example 1.
[0060] Example 3 This embodiment discloses a preparation process for low-bleeding concrete using graded utilization of manufactured sand and gravel powder, employing a high-value combination of particle size, total stone powder, slurry preparation time, and segmented feeding ratio.
[0061] In each cubic meter of concrete, the amounts of F1, F2, and F3 are 10 kg, 50 kg, and 60 kg, respectively, and the amount of manufactured sand is 728 kg. The amounts of other materials are the same as in Example 1. The dry weight ratio of F1, F2, and F3 is 1:5:6, and the total amount is 120 kg. The D50 of F1 is 5.0 μm, the D90 is 8.0 μm, and particles smaller than 2 μm account for 18.0%; the D10 of F2 is 9.0 μm, the D50 is 22.0 μm, and the D90 is 35.0 μm; the D10 of F3 is 32.0 μm, the D50 is 70.0 μm, and the D90 is 100.0 μm. The D50 of cement is 18.3 μm, the ratio of F2 to cement D50 is 1.20, and the ratio of F3 to cement D50 is 3.83.
[0062] During pulping, 6.700 kg of water (part 1), 51.0 g of dispersant product, 6.00 g of dry polymer, and 10.0 g of defoamer product were added. The effective solids of the dispersant were 50.0 g, which is 0.50 parts by weight per 100 parts by weight of F1; the dry polymer was 0.060 parts by weight; the defoamer product was 0.10 parts by weight; and the pulp solids content was 60.0%. The Qs of this batch of F1 were 5.88 mg / g, and the effective solids of the dispersant added were 85.0% of the Qs. F1 was dispersed at 2000 r / min for 10 min and then subjected to a site-occupancy treatment for 20 min; the dry polymer was stirred at 600 r / min for 5 min and then matured for 30 min.
[0063] S3: Dry mixing for 40 s; S4: Dry mixing for 30 s. S5: Add 131.392 kg of added water and 5.76 kg of the main polycarboxylate superplasticizer product. The total water entering the system is 136.000 kg, accounting for 85.0% of the total water. Wet mixing for 70 s. S6: Add all of the F1 ultrafine water-controlled slurry, 16.781 kg of added water, and 0.64 kg of the main polycarboxylate superplasticizer product. Stir for 60 s. The manufactured sand used in this example, along with F1 to F3, all came from the same limestone manufactured sand production line. The content of 0.075–0.15 mm particles in the manufactured sand and F3 was 3.2% and 46.5%, respectively. This fraction accounted for 6.5% of the combined fine aggregate, with a fineness modulus of 2.56. The remaining equipment and operating conditions were the same as in Example 1.
[0064] Example 4 This embodiment discloses a preparation process for low-bleeding concrete using graded and utilized manufactured sand and gravel powder, employing granite powder, wet grading, and polyether phosphate dispersant.
[0065] Wet grading of fine stone powder from the same rock source collected by the granite manufactured sand production line was performed using a hydrocyclone. Each particle size was dried at 105℃ until the mass difference between two consecutive weighings was no greater than 0.1% before use. The manufactured sand in this embodiment was also taken from the same granite manufactured sand production line. In each cubic meter of concrete, the dosages of F1, F2, and F3 were 10 kg, 40 kg, and 70 kg, respectively, and the dosage of manufactured sand was 728 kg. The dosages of cement, fly ash, mineral powder, coarse aggregate, total water, and main polycarboxylate superplasticizer were the same as in Example 1. The dry mass ratio of the three stone powders was 1:4:7, and the total dosage was 120 kg. F1 has a D50 of 3.8 μm and a D90 of 7.4 μm; F2 has a D10 of 6.5 μm, a D50 of 14.0 μm, and a D90 of 29.0 μm; F3 has a D10 of 31.0 μm, a D50 of 68.0 μm, and a D90 of 96.0 μm. The cement D50 is 11.7 μm. The ratio of F2 to cement D50 is 1.20, and the ratio of F3 to cement D50 is 5.81.
[0066] The dispersant was the same powdered polyether phosphate as in Example 1, with an active ingredient content of 98.0%, a number-average molecular weight of 2800, and a phosphorus content of 1.8%. During pulping, 9.272 kg of water was added as the first portion, followed by 40.8 g of the polyether phosphate product, which provided 40.0 g of effective dispersant solids; subsequently, 5.00 g of dry polymer was added. The effective dispersant solids and dry polymer, calculated per 100 parts by weight of F1, were 0.40 parts by weight and 0.050 parts by weight, respectively; the slurry solids content was 52.0%. The amphoteric water-controlling polymer had a relative weight-average molecular weight of 2 million and cationic structural units accounting for 20 mol%. The Qs measured using this single polyether phosphate in this batch of F1 was 5.00 mg / g, and the actual amount added was 4.00 mg / g, i.e., 80.0% of Qs.
[0067] S5 contains 115.904 kg of added water and 5.12 kg of the main polycarboxylate superplasticizer product; S6 contains all of the F1 ultrafine water-controlled slurry, 29.704 kg of added water, and 1.28 kg of the main polycarboxylate superplasticizer product. The content of 0.075–0.15 mm particles in the manufactured sand and F3 is 3.1% and 40.0%, respectively, and this fraction accounts for 6.3% of the combined fine aggregate, with a fineness modulus of 2.66. The 9.272 kg of water in the first part is all deionized water and is included in the total water consumption of 160 kg. The remaining slurry preparation, mixing equipment, and operating parameters are the same as in Example 1.
[0068] Example 5 This embodiment discloses a preparation process for low-bleeding concrete using graded and utilized manufactured sand and gravel powder, employing basalt powder, cyclone grading, and polycarboxylate dispersant.
[0069] A two-stage cyclone classifier was used to classify the fine stone powder raw materials from the same rock source collected by the basalt manufactured sand production line; the manufactured sand in this embodiment was also taken from the same basalt manufactured sand production line. In each cubic meter of concrete, the amounts of F1, F2, and F3 were 5 kg, 20 kg, and 20 kg respectively, and the amount of manufactured sand was 803 kg. The amounts of cement, fly ash, mineral powder, coarse aggregate, total water, and main polycarboxylate superplasticizer were the same as in Example 1. The dry mass ratio of the three stone powders was 1:4:4, and the total amount was 45 kg. The D50 of F1 was 2.6 μm and the D90 was 6.4 μm; the D10 of F2 was 5.8 μm, the D50 was 13.5 μm, and the D90 was 27.0 μm; and the D10 of F3 was 27.0 μm, the D50 was 50.0 μm, and the D90 was 88.0 μm.
[0070] The dispersant was a polycarboxylate dispersant with a solid content of 30.0%, a carboxyl density of 0.45 mmol / g, and a number-average molecular weight of 36,000. During pulping, 5.401 kg of the first batch of added water, 46.7 g of the polycarboxylate dispersant product, and 1.50 g of dry polymer were added. This dispersant product contained 14.0 g of effective solids and carried over 32.7 g of carrier water; the carrier water was included in the water in the F1 ultrafine water-controlled pulp and in the total water volume of 160 kg. The effective solids of the dispersant, calculated per 100 parts by weight of F1, were 0.28 parts by weight, and the dry polymer was 0.030 parts by weight, resulting in a pulp solid content of 48.0%. The amphoteric water-controlled polymer had a relative weight-average molecular weight of 600,000, with cationic structural units accounting for 8 mol%. The Qs of this batch of F1 was 3.50 mg / g, and the actual amount added was 2.80 mg / g, which is 80.0% of the Qs.
[0071] S5 contains 115.904 kg of added water and 5.12 kg of the main polycarboxylate superplasticizer product; S6 contains all of the F1 ultrafine water-controlled slurry, 33.543 kg of added water, and 1.28 kg of the main polycarboxylate superplasticizer product. The content of 0.075–0.15 mm particles in the manufactured sand and F3 is 2.9% and 20.0%, respectively, and this fraction accounts for 3.3% of the combined fine aggregate, with a fineness modulus of 2.83. The remaining slurry preparation and concrete mixing parameters are the same as in Example 1.
[0072] Example 6 This embodiment discloses a preparation process for low-bleeding concrete using graded utilization of manufactured sand and gravel powder, which is used to verify the lower end combination of a wide range of mass ratios of F1, F2 and F3, as well as the upper limit of F1 dosage.
[0073] Using the same source of fine stone powder and dynamic air classification equipment from the low-clay-content marble manufactured sand production line, the manufactured sand in this embodiment also comes from this production line. In each cubic meter of concrete, the amounts of F1, F2, and F3 are 15 kg, 30 kg, and 45 kg, respectively, with 758 kg of manufactured sand. The amounts of cement, fly ash, mineral powder, coarse aggregate, total water, and main polycarboxylate superplasticizer are the same as in Example 1. The dry mass ratio of the three stone powders is 1:2:3, with a total amount of 90 kg. The D50 of F1 is 3.0 μm and the D90 is 6.6 μm; the D10 of F2 is 6.8 μm, the D50 is 15.0 μm, and the D90 is 29.5 μm; the D10 of F3 is 29.5 μm, the D50 is 45.0 μm, and the D90 is 83.0 μm. The particle size distribution overlap coefficient between F1 and F2 is 14.8%, and the particle size distribution overlap coefficient between F2 and F3 is 16.5%.
[0074] During pulping, 19.500 kg of water (part 1), 15.33 g of dispersant product, and 0.75 g of dry polymer were added. The effective solids of the dispersant were 15.02 g, which is 0.100 parts by weight per 100 parts by weight of F1; the dry polymer was 0.005 parts by weight, and the solids content of the pulp was 43.5%. The Qs of this batch of F1 was 1.54 mg / g, and the effective solids of the dispersant added was 1.001 mg / g, which is 65.0% of the Qs. In S5, 115.904 kg of added water and 5.12 kg of main polycarboxylate superplasticizer product were added; in S6, all of the F1 ultrafine water-controlled pulp, 19.476 kg of added water, and 1.28 kg of main polycarboxylate superplasticizer product were added. The content of 0.075–0.15 mm particles in the manufactured sand and F3 was 3.0% and 14.0%, respectively, and this fraction accounted for 3.6% of the combined fine aggregate, with a fineness modulus of 2.95. The remaining pulping and mixing parameters are the same as in Example 1.
[0075] Example 7 This embodiment discloses a preparation process for low-bleeding concrete using graded utilization of manufactured sand and gravel powder, which is used to verify the upper-end combination of a wide range of mass ratios of F1, F2 and F3, as well as the lower limit of F1 dosage.
[0076] Using the same source of fine stone powder and dynamic air classification equipment from the porous basaltic tuff manufactured sand production line, the manufactured sand in this embodiment also comes from this production line. In each cubic meter of concrete, the amounts of F1, F2, and F3 are 3 kg, 18 kg, and 27 kg, respectively, with 800 kg of manufactured sand. The amounts of cement, fly ash, mineral powder, coarse aggregate, total water, and main polycarboxylate superplasticizer are the same as in Example 1. The dry weight ratio of the three stone powders is 1:6:9, with a total amount of 48 kg. The D50 of F1 is 2.0 μm and the D90 is 5.9 μm; the D10 of F2 is 5.5 μm, the D50 is 11.0 μm, and the D90 is 25.0 μm; and the D10 of F3 is 25.5 μm, the D50 is 42.0 μm, and the D90 is 80.0 μm. The particle size distribution overlap coefficient between F1 and F2 is 19.8%, and the particle size distribution overlap coefficient between F2 and F3 is 19.6%.
[0077] During pulping, 2.018 kg of water (part 1), 24.5 g of dispersant product, and 3.00 g of dry polymer were added. The effective solids of the dispersant were 24.0 g, which is 0.80 parts by weight per 100 parts by weight of F1; the dry polymer was 0.10 parts by weight, and the solids content of the pulp was 60.0%. The Qs of this batch of F1 was 9.41 mg / g, and the effective solids of the dispersant added was 85.0% of Qs. In S5, 115.904 kg of added water and 5.12 kg of the main polycarboxylate superplasticizer product were added; in S6, all of the F1 ultrafine water-controlled pulp, 36.958 kg of added water, and 1.28 kg of the main polycarboxylate superplasticizer product were added. The content of 0.075–0.15 mm particles in the manufactured sand and F3 was 3.1% and 10.0%, respectively, and this fraction accounted for 3.3% of the combined fine aggregate, with a fineness modulus of 2.70. The remaining pulping and mixing parameters were the same as in Example 1.
[0078] Example 8 This embodiment discloses a preparation process for low-bleeding concrete using graded and utilized manufactured sand and gravel powder, used to verify the single-factor effect of a 65.0% Qs lower limit. Compared with Example 1, only the effective solid content of the dispersant was adjusted to 20.8 g, i.e., 2.60 mg / g, 65.0% of Qs; the corresponding dosage of the dispersant product with an active ingredient content of 98.0% was 21.2 g. All other raw materials, particle size and dosage of the graded stone powder, water-powder mass ratio, dosage of amphoteric water-controlling polymer and defoamer, and slurry preparation and concrete mixing parameters were the same as in Example 1.
[0079] Example 9 This embodiment discloses a preparation process for low-bleeding concrete using graded and utilized manufactured sand and gravel powder, used to verify the single-factor effect at the 75.0% Qs midpoint. Compared with Example 1, only the effective solid content of the dispersant was adjusted to 24.0 g, i.e., 3.00 mg / g, 75.0% of Qs; the dosage of the dispersant product with an active ingredient content of 98.0% was 24.5 g. All other raw materials, particle size and dosage of the graded stone powder, water-powder mass ratio, dosage of amphoteric water-controlling polymer and defoamer, and slurry preparation and concrete mixing parameters were the same as in Example 1.
[0080] Example 10 This embodiment discloses a preparation process for low-bleeding concrete using graded and utilized manufactured sand and gravel powder, used to verify the single-factor effect of the 85.0% Qs upper limit. Compared with Example 1, only the effective solid content of the dispersant was adjusted to 27.2 g, i.e., 3.40 mg / g, 85.0% of Qs; the corresponding dosage of the dispersant product with an active ingredient content of 98.0% was 27.8 g. All other raw materials, particle size and dosage of the graded stone powder, water-powder mass ratio, dosage of amphoteric water-controlling polymer and defoamer, and slurry preparation and concrete mixing parameters were the same as in Example 1.
[0081] Comparative Example 1 This comparative example discloses a concrete preparation process utilizing manufactured sand and gravel powder, serving as a conventional overall control without functional grading and phased utilization. 88 kg of the same batch of raw limestone powder was added together with cement, fly ash, and mineral powder in step S4, without preparing F1 ultrafine water-controlled slurry; the raw stone powder had a D10 of 3.1 μm, a D50 of 19.8 μm, and a D90 of 71.0 μm. In step S5, 115.904 kg of added water and 5.12 kg of the main polycarboxylate superplasticizer product were added, and wet-mixed for 55 s; in step S6, 38.974 kg of added water, 1.28 kg of the remaining main polycarboxylate superplasticizer product, and 2.40 g of the same defoamer product as in Example 1 were added, and stirred for 45 s. The total water usage remained 160 kg, and the total amount of main polycarboxylate superplasticizer, the amount of defoamer product, and the total mixing time were all the same as in Example 1.
[0082] Comparative Example 2 This comparative example discloses a concrete preparation process for the graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that 8 kg of F2 is used instead of 8 kg of F1, and F2 slurry is prepared according to the Qs measured by F2. The Qs of this batch of F2 is 2.20 mg / g, and the effective solids of the dispersant added is 1.76 mg / g, which is 80.0% of Qs. The slurry preparation and S6 addition conditions are the same as in Example 1. The total amount of F3 and stone powder remains unchanged, indicating that under the condition of equal Qs ratio control according to the corresponding stone powder adsorption capacity, replacing F1 with F2 cannot obtain the same water-controlled slurry rheological behavior and anti-bleeding effect as F1.
[0083] Comparative Example 3 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that 32 kg F3 is used instead of 32 kg F2 and added at S4, while the total amount of F1 and stone powder remains unchanged. This is used to verify the independent role of F2 paste-filling grade stone powder.
[0084] Comparative Example 4 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that 48 kg F2 is used instead of 48 kg F3 and added at S3, while the total amount of F1 and stone powder remains unchanged. This is used to verify the independent role of F3 micro-aggregate grade stone powder.
[0085] Comparative Example 5 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that the effective solid content of the dispersant is adjusted to 60.0% of Qs, which is lower than the lower limit of 65.0%. The other conditions are the same as those in Example 1.
[0086] Comparative Example 6 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that the effective solid content of the dispersant is adjusted to 90.0% of Qs, which is higher than the upper limit of 85.0%. The other conditions are the same as in Example 1.
[0087] Comparative Example 7 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that the amphoteric water-controlling polymer is not added when preparing F1 ultrafine water-controlling slurry. All other conditions are the same as in Example 1.
[0088] Comparative Example 8 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that after F1 is dispersed for 6 min, a 12 min surface occupancy treatment is not performed, and the amphoteric water-controlling polymer is added immediately. The other conditions are the same as in Example 1.
[0089] Comparative Example 9 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that after 20 seconds of dry mixing in S4 and before S5, all of the F1 ultrafine water-controlling slurry is added and stirred at 32 r / min for 5 seconds; then S5 is carried out and the wet mixing time is adjusted to 50 seconds; in S6, only the remaining admixture water and the remaining main polycarboxylate superplasticizer product are added and stirred for 45 seconds. The total water usage, the metering standards for each liquid component, and the total stirring time after S4 are the same as in Example 1, used to verify the effect of the timing of adding the F1 ultrafine water-controlling slurry.
[0090] Comparative Example 10 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that F3 is not added in S3, and 48 kg of F3 is moved to S4 and added together with cement, fly ash, mineral powder and F2. The other conditions are the same as in Example 1.
[0091] Comparative Example 11 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that all 6.40 kg of the main polycarboxylate superplasticizer product is added in S5, and no main polycarboxylate superplasticizer is added in S6. In S5, 114.880 kg of added water and 6.40 kg of the main polycarboxylate superplasticizer product are added, and the product carries in 5.120 kg of carrier water, bringing the total water entering the system in this step to 120.000 kg. In S6, all of the F1 ultrafine water-controlling slurry and 31.998 kg of added water are added, and no more superplasticizer is added. After including the water in the F1 ultrafine water-controlling slurry and the carrier water of the defoamer, the total water entering the system in this step is 40.000 kg. The total water usage of 160 kg and the water distribution in S5 and S6 remain unchanged, and the other conditions are the same as in Example 1.
[0092] Comparative Example 12 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that all water that can be added separately, except for water in F1 ultrafine water-controlling slurry, defoamer carrier water, and S6 water-reducing agent carrier water, is added in step S5. In step S5, 146.878 kg of external water and 5.12 kg of main polycarboxylate superplasticizer product are added, and the product carries in 4.096 kg of carrier water. The total water entering the system in this step is 150.974 kg, accounting for 94.4% of the total water used. In step S6, no external water is added, but all F1 ultrafine water-controlling slurry and 1.28 kg of main polycarboxylate superplasticizer product are added. After including 8.000 kg of the first part of water, 0.00168 kg of defoamer carrier water, and 1.024 kg of water-reducing agent carrier water, the total water entering the system in this step is 9.026 kg, accounting for 5.6% of the total water used. The main polycarboxylate superplasticizer was still added in stages at 80.0% and 20.0%, and the other conditions were the same as in Example 1.
[0093] Comparative Example 13 This comparative example discloses a concrete preparation process for the graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that the separation sharpness of the air classifier is reduced, so that the particle size distribution overlap coefficient of adjacent particle sizes exceeds 20%, while maintaining that the D10, D50, and D90 of each particle size falls within the scope defined in claim 1. The D50 of F1 is 3.2 μm and the D90 is 8.0 μm; the D10 of F2 is 5.0 μm, the D50 is 16.0 μm, and the D90 is 35.0 μm; the D10 of F3 is 25.0 μm, the D50 is 55.0 μm, and the D90 is 100.0 μm. The particle size distribution overlap coefficients of F1 and F2, and F2 and F3 are 23.5% and 22.8%, respectively; the amount of each particle size, the batch of raw materials, and other conditions are the same as in Example 1.
[0094] Comparative Example 14 This comparative example discloses a concrete preparation process for graded utilization of manufactured sand and gravel powder. The only difference from Example 1 is that the amounts of F1, F2, and F3 are adjusted to 5.18 kg, 33.65 kg, and 49.17 kg, respectively, with a dry weight ratio of 1:6.5:9.5, and the total amount of the three grades of stone powder remains 88.00 kg. The first part of water, dispersant, amphoteric water-controlling polymer, and defoamer in the F1 ultrafine water-controlling slurry are all adjusted proportionally to the mass of F1 relative to Example 1: the first part of water is 5.180 kg, the dispersant product is 16.914 g, of which the effective solids are 16.576 g, the amphoteric water-controlling polymer is 2.072 g, and the defoamer product is 1.554 g; thus, the water / F1 mass ratio, the 80.0% Qs surface occupancy ratio, the amphoteric water-controlling polymer / F1 mass ratio, the defoamer / F1 mass ratio, and the slurry solid content are consistent with those of Example 1. S5 still includes 115.904 kg of added water and 5.12 kg of the main polycarboxylate superplasticizer product; S6 includes all of the F1 ultrafine water-controlling slurry, 33.795 kg of added water, and 1.28 kg of the main polycarboxylate superplasticizer product, maintaining the total water consumption of the concrete at 160 kg / m³. The amount of manufactured sand and the remaining slurry preparation, feeding, and mixing conditions are the same as in Example 1. The content of 0.075–0.15 mm particles in manufactured sand and F3 is 3.0% and 24.0%, respectively, with this fraction accounting for 4.3% of the composite fine aggregate, and a fineness modulus of 2.75.
[0095] 1. Detection of saturated adsorption capacity At 24–26 °C, 50.00 g of stone powder was mixed with 50.00 g of deionized water. A uniform initial addition gradient was established, with each gram of stone powder containing 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 8.0, 10.0, and 12.0 mg of dispersant effective solids. When the pre-test showed the plateau was between two adjacent points, the number of measurement points was increased to 0.5 mg / g within that interval. At each addition point, the mixture was mixed at 1500 r / min for 6 min and equilibrated for 30 min, followed by centrifugation at a relative centrifugal force of 11900 × g for 10 min. The supernatant filtered through a 0.22 μm aqueous filter membrane was analyzed using a total organic carbon analyzer. For each single dispersant, standard solutions with effective solids concentrations of 0.05, 0.10, 0.50, 1.00, 2.00, 5.00, and 10.00 mg / g were prepared in liquid phase. Calibration curves were established between the total organic carbon response value and the effective solids concentration, with a linear correlation coefficient R² not less than 0.999. When the supernatant concentration was higher than 10.00 mg / g, quantitative dilution with deionized water was performed at 2, 5, or 10 times to bring the detection value into the calibration range, and then multiplied by the dilution factor to convert the original solution concentration. The background of dissolved organic carbon from stone powder was subtracted using a blank solution of stone powder without dispersant. The mass concentration of the dispersant in the equilibrium liquid phase is denoted by c, in mg / g liquid phase; the initial effective solid mass of the dispersant is denoted by m0, in mg; the mass of stone powder is denoted by mF, in g; the initial mass of water in the liquid phase before adding the dispersant is denoted by m_W, in g, where the carrier water brought in by the liquid dispersant product is included in m_W; the total mass of the liquid phase in the equilibrium system is denoted by m_L, in g, where m_L is not the actual mass of the supernatant recovered after centrifugation. Ignoring the slight influence of inorganic leaching from the stone powder on the total mass of the liquid phase, the mass of unadsorbed dispersant m_free satisfies m_free = c × m_L and m_L = m_W + m_free / 1000 with respect to the liquid phase mass. Therefore, m_L = m_W / (1-c / 1000); the adsorption capacity per unit mass of stone powder is then calculated using q = (m0 - c × m_L) / mF. The equilibrium liquid phase that was not actually recovered and remained in the pores of the precipitate layer, along with the unadsorbed dispersant therein, are all included in m_L. The relative increase at adjacent addition points is calculated as (qi-qi-1) / qi-1×100%. When two consecutive increases are less than 2.0%, the arithmetic mean of the adsorption amounts at the corresponding three plateau points is taken as Qs. Three samples of each batch of stone powder were independently tested, and the arithmetic mean of the three results was used in the example.
[0096] 2. Particle size, particle size distribution overlap coefficient, and detection of combined fine aggregates The D10, D50, and D90 of cement and stone powder of various particle sizes were determined using a laser diffraction particle size analyzer. For stone powder testing, 1.00 g of sample was added to 100 mL of deionized water, along with 0.05 g of sodium hexametaphosphate, and ultrasonically dispersed at 600 W for 3 min before testing. For cement testing, 1.00 g of sample was added to 100 mL of anhydrous isopropanol, and ultrasonically dispersed at 200 W for 1 min in a sealed sample cell before testing to avoid hydration altering the original particle state. Each sample was independently sampled three times, with three cycles of measurement each time. The arithmetic mean of the three independent sample measurements was used as the result. In the examples, the D50 / cement D50 of F2 and the D50 / cement D50 of F3 were verified using the cement D50 obtained by this non-aqueous medium method. The volume fractions of each particle size channel output by the instrument are normalized so that the sum of the volume fractions of all particle size channels is 1. Under the same particle size channel boundary, the particle size distribution overlap coefficient of adjacent particle sizes is calculated as O=Σkmin(Pik,Pjk)×100%, where Pik and Pjk are the normalized volume fractions of two adjacent particle sizes in the k-th particle size channel, and the sum covers all particle size channels output by the instrument. The content of 0.075-0.15 mm particles in manufactured sand and F3 itself and the fineness modulus of the combined fine aggregate are tested according to JGJ 52—2006 "Standard for Quality and Test Methods of Sand and Stone for Ordinary Concrete"; the mass ratio of this grade in the combined fine aggregate is calculated as P=(mS×PS+mF3×PF3) / (mS+mF3), where mS and mF3 are the masses of manufactured sand and F3, respectively, and PS and PF3 are the mass ratios of 0.075-0.15 mm particles of each of them.
[0097] Table 1. Overlap coefficient of stone powder particle size distribution with adjacent particle sizes Table 2 Weighted Calculation of Grade III Stone Powder Dosage and Blended Fine Aggregate Gradation 3. F1 Ultrafine Water-Controlled Slurry Rheological Properties Testing The matured slurry was placed in a constant temperature environment of 25℃ for 10 min and tested using a coaxial cylindrical rotor rheometer. The inner cylinder diameter was 27.0 mm, the outer cylinder inner diameter was 29.0 mm, the radial shear gap was 1.0 mm, the effective immersion height was 40.0 mm, and the contact surfaces of the inner and outer cylinders had a fine-toothed anti-slip structure. First, a shearing was performed at 50 s⁻¹ for 60 s, and the apparent viscosity at the 60th s was taken as the apparent viscosity before shearing η₀. Then, a shearing was performed at 500 s⁻¹ for 60 s, and the apparent viscosity at the 60th s was taken as the high-shear apparent viscosity ηh. The 500 s⁻¹ shearing was stopped and the slurry was allowed to stand for 5 min, then a shearing was performed at 50 s⁻¹ for 10 s, and the apparent viscosity at the 10th s was taken as the recovered apparent viscosity η₅. The viscosity decrease rate was calculated as (η₀-ηh) / η₀×100%, and the apparent viscosity recovery rate was calculated as η₅ / η₀×100%. Three parallel slurries were prepared independently for each sample. The data in the table are arithmetic means. The coefficients of variation of η0, ηh and η5 for each group are not higher than 5.0%.
[0098] Table 3 Results of slurry rheological property testing The standard deviations of the recovery rates for the core Qs gradient groups are as follows: 1.1, 1.0, 0.9, 1.2, 0.8, and 0.9 percentage points for Examples 8, 9, 1, 10, Comparative Example 5, and Comparative Example 6, respectively. Each standard deviation was calculated from three independent parallel slurry results.
[0099] 4. Testing of concrete workability, air content, and general bleeding rate. The initial slump, air content, and ordinary bleeding tests were conducted in accordance with GB / T 50080—2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". Initial slump and air content were tested immediately after the concrete was discharged from the mixer. The ordinary bleeding test continued until three consecutive observations showed no increase in bleeding. The bleeding rate B was calculated as B=W / [ms×(mw / mt)]×100%, where W is the cumulative bleeding mass, ms is the mass of the concrete sample placed in the bleeding container, mw is the total water mass after including all liquid water in the mix proportion, and mt is the total mass of all raw materials calculated based on actual input. For liquid admixtures, their product mass was only included in mt once; although the liquid water was included in mw, it was not counted again as an independent water mass in mt. The 60-minute slump test was performed using the intermittent re-stirring procedure specified in this application: the remaining mixture was covered and allowed to stand, then stirred at 32 r / min for 15 s every 20 minutes. At 60 minutes, the slump test was conducted according to the operating procedures specified in GB / T 50080—2016. To compare the experimental groups, three trays were prepared for each sample independently. The slump, air content, and ordinary bleeding rate were measured once for each tray. The arithmetic mean and coefficient of variation of the three tray results were calculated. The coefficients of variation for slump, air content, and ordinary bleeding rate for each group were no higher than 3.5%, 5.0%, and 8.8%, respectively.
[0100] Table 4. Test results of concrete workability, air content, and ordinary bleeding rate. The standard deviations of the general bleeding rate for the core Qs gradient group are as follows: 0.03, 0.02, 0.02, 0.03, 0.10, and 0.08 percentage points for Examples 8, 9, 1, 10, Comparative Example 5, and Comparative Example 6, respectively. Each standard deviation was calculated from the results of three independent mixing batches.
[0101] 5. Concrete pressure bleeding rate test The test was conducted according to the pressure bleeding rate test method for cement concrete mixtures in JTG 3420—2020 "Test Procedures for Cement and Cement Concrete in Highway Engineering" (T 0531). The mixture within 3 minutes of being removed from the mixer was loaded into a pressure bleeding apparatus, compacted, and covered. The bleeding volumes V10 and V140 were recorded after 10 s and 140 s of constant pressure (3.2 MPa), respectively, with each V10 and V140 accurate to 1 mL. The pressure bleeding rate for each batch was calculated as Bp = V10 / V140 × 100%, with the calculated Bp result accurate to 1%. Three batches were prepared independently for each sample, and each batch was tested once. The pressure bleeding rate in the table is the arithmetic mean of the Bp values from the three batches, rounded to 1%. The standard deviation and coefficient of variation of the pressure bleeding rate were calculated based on the individual Bp values of the three batches. Tables V10 and V140 only list the arithmetic mean of the three readings and rounded to 1 mL to characterize the level of oozing volume. The pressure oozing rate in the table will not be calculated from V10 and V140. The coefficient of variation of the pressure oozing rate of each group is no higher than 7.0%.
[0102] Table 5 Results of concrete pressure bleeding rate test The standard deviations of the pressure bleeding rate for the core Qs gradient groups are as follows: 1.2, 0.9, 0.8, 0.9, 2.1, and 1.9 percentage points for Examples 8, 9, 1, 10, Comparative Example 5, and Comparative Example 6, respectively. Each standard deviation was calculated based on the Bp results of each of the three discs, calculated using V10 / V140 and rounded to 1%.
[0103] 6. Testing of concrete rheological properties The mixture was tested within 8 minutes after discharge using a blade-type concrete rheometer at 18–22℃. The blade diameter and height were both 100 mm, the inner diameter of the test cylinder was 250 mm, and the sample loading height was 220 mm. The lower edge of the blade was 60 mm from the bottom of the cylinder, and the height of the mixture above the upper edge of the blade was no less than 60 mm. A pre-shear was performed at 0.50 r / s for 30 s, followed by a 30-s resting period. Shearing was then performed sequentially at 0.50, 0.40, 0.30, and 0.20 r / s, with each stage held for 20 s. The average torque over the last 5 s was recorded. The rotational speed was converted to r / min, and a linear fit was performed using T = T0 + hN, where T is the torque, N is the rotational speed, T0 is the yield torque, and h is the plastic viscosity index. The coefficient of determination R² was no less than 0.990. A smaller h indicates a lower increase in viscous resistance due to the same increase in rotational speed. Each sample was prepared independently in 3 trays, and each tray was tested once. The data in the table is the arithmetic mean of the 3 trays. The coefficients of variation of T0 and h are not higher than 6.0%.
[0104] Table 6 Results of concrete rheological property tests 7. Concrete compressive strength testing Cube specimens with a side length of 150 mm were prepared according to GB / T 50081—2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The compressive strength was tested after curing in a standard curing room at 20℃ and a relative humidity of not less than 95% for 28 days. Three specimens were prepared for each batch of concrete, and a total of nine specimens were tested for each sample. The representative values of the three specimens from each batch were first calculated, and then the arithmetic mean of the three representative values was used as the result in the table. The coefficient of variation of the representative strength values for each group was not higher than 4.5%.
[0105] Table 7 Results of 28-day compressive strength test of concrete Tables 1 and 2 show that Examples 1–7 cover the particle size range of the three grades of stone powder, the mass ratio of 1:(2–6):(3–9), the dosage of F1 of 3–15 kg / m³, the dosage of F2 of 15–50 kg / m³, the dosage of F3 of 20–70 kg / m³, and the total amount of three grades of stone powder of 45–120 kg / m³. Examples 8–10 use the particle size and proportion of Example 1 to isolate the Qs proportion variable. The overlap coefficient of adjacent particle size distributions in Examples 1–10 is no higher than 20.0%. Table 2 lists the proportion of 0.075–0.15 mm particles of manufactured sand and F3 itself, and obtains the combined fine aggregate gradation proportion of 3.0%–6.5% by weighting the two by mass, with a combined fine aggregate fineness modulus of 2.56–2.95. The results indicate that F3 participates in the fine-end particle size distribution adjustment of manufactured sand, fills the fine particle range, and reduces the large-scale voids between aggregate particles; the specific contribution of the coarser tail of F3 entering the 0.075-0.15 mm range to the composite gradation can be verified by Table 2.
[0106] Table 3 shows that the η0 of the slurries in Examples 1-10 ranged from 145 to 485 mPa·s, with viscosity reduction rates of 33.1% to 63.1% and recovery rates of 36.1% to 74.5%. Specifically, Examples 8, 9, and 10 only set the dispersant dosage to 65.0%, 75.0%, and 85.0% of Qs, respectively, resulting in recovery rates of 58.7%, 60.4%, and 59.0%. Combined with the 80.0% Qs of Example 1, the 60.0% Qs of Comparative Example 5, and the 90.0% Qs of Comparative Example 6, a strict univariate gradient was formed: out-of-range – lower limit – midpoint – preferred point – upper limit – out-of-range. The standard deviation of the above six groups of recovery rates ranged from 0.8 to 1.2 percentage points. The results of Comparative Example 2 show that, under the condition of equal Qs ratio adjustment according to the corresponding stone powder adsorption capacity, replacing F1 with F2 still cannot obtain the same slurry rheological behavior as F1; after removing the amphoteric water-controlling polymer in Comparative Example 7 and removing the surface occupation treatment in Comparative Example 8, the recovery rate dropped to 23.8% and 33.1%, respectively.
[0107] Significant performance changes were observed in the core Qs gradient around 60.0%Qs to 65.0%Qs and 85.0%Qs to 90.0%Qs, which is speculated to be related to the F1 particle surface occupancy state crossing suitable ranges: below 65.0%Qs, the dispersant occupancy is insufficient, and strong and difficult-to-fully-recover local aggregations may form between the ultrafine particles and the amphoteric water-controlling polymer; between 65.0% and 85.0%Qs, particle pre-dispersion and reversible polymer association are relatively balanced; above 85.0%Qs, the number of sites available for the amphoteric water-controlling polymer to participate in interfacial association may decrease, and the static recovery network weakens. The above mechanism is a speculation based on the performance change trend. The measured results outside the range both show a decrease in recovery rate and a higher pressure bleeding rate compared to the examples within the range.
[0108] Table 4 shows that the ordinary bleeding rate of Examples 1-10 was 0.3%-0.7%, the slump retention rate at 60 min was 83.7%-88.6%, and the air content was 2.3%-2.7%. The air content of each comparative example was 2.3%-2.7%, which is at the same level as the examples. Therefore, the difference in ordinary bleeding rate cannot be attributed to changes in air content. When the amount of defoamer, total water, total amount of water-reducing agent, and stirring time were kept consistent in Comparative Example 1, the ordinary bleeding rate was 2.6%. After changing the particle size of F1, F2, and F3 in Comparative Examples 2-4, the ordinary bleeding rate was 1.4%-2.2%. After changing the timing of adding F1 slurry, the timing of adding F3 slurry, and the segmentation method of water-reducing agent or water in Comparative Examples 9-12, the ordinary bleeding rate increased to 1.2%-1.7%.
[0109] Table 5 shows that the pressure bleeding rate of Examples 1-10 was 24%-32%, lower than that of Comparative Examples 1-14 (49%-58%), indicating that the early drainage rate of the Examples under pressure conditions was significantly lower than that of the Comparative Examples. This result is used to demonstrate relative improvement and is not an absolute evaluation of reaching the recommended limits for specific engineering projects. The standard deviation of the pressure bleeding rate of the core Qs gradient group 6 was 0.8-2.1 percentage points. Table 6 shows that the plastic viscosity index of Examples 1-10 was 0.68-0.80 N·m / (r / min), lower than that of Comparative Examples 1-14 (0.97-1.18 N·m / (r / min); at the same time, the yield torque of the Examples was 8.6-9.7 N·m, indicating that the system had a relatively stable structure during the static stage, while the increase in viscous resistance was low with increasing rotational speed. Comparative Example 13, with other formulation and preparation conditions remaining unchanged, increased the particle size distribution overlap coefficients of F1 / F2 and F2 / F3 to 23.5% and 22.8%, respectively, by reducing the classification sharpness. This was accompanied by the adjacent particle size distribution boundaries moving closer to each other, and the ordinary bleeding rate increased to 1.9%. This indicates that maintaining a high classification sharpness and limiting the overlap of adjacent particle size distributions is beneficial for the three grades of stone powder to play their respective roles. Comparative Example 14, with the three-grade mass ratio adjusted outside the range, had an ordinary bleeding rate of 1.6%. Table 7 shows that the 28-day compressive strength of Examples 1–10 was 44.2–52.4 MPa, and the low bleeding and low plastic viscosity index did not come at the cost of a significant reduction in hardening strength.
[0110] Therefore, the particle size distribution of the three-grade stone powder, the surface occupancy treatment of 65.0%–85.0% Qs, the orderly preparation of F1 ultrafine water-controlling slurry, and the phased feeding of solid and liquid components, compared with the control ratio that did not adopt the above-mentioned graded utilization and water-controlling slurry treatment, jointly reduce ordinary bleeding and pressure bleeding, while reducing the plastic viscosity index of concrete and maintaining a high slump retention rate and stable 28-day compressive strength.
[0111] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A process for preparing low-bleeding concrete using graded and utilized manufactured sand and gravel powder, characterized in that, Includes the following steps: S1. The same rock-source fine stone powder raw material generated during the production of manufactured sand and obtained through dust collection or fine material collection is classified to obtain F1 ultrafine water-controlled stone powder, F2 slurry-filled stone powder and F3 micro-aggregate stone powder. The F1 ultrafine water-controlled stone powder has a D50 of 1.5–5.0 μm and a D90 of no more than 8 μm; the F2 slurry-filled stone powder has a D10 of no less than 5 μm, a D50 of 10–22 μm, and a D90 of no more than 35 μm; the F3 micro-aggregate stone powder has a D10 of no less than 25 μm, a D50 of 40–70 μm, and a D90 of no more than 100 μm; and the dry mass ratio of the F1 ultrafine water-controlled stone powder, the F2 slurry-filled stone powder, and the F3 micro-aggregate stone powder is 1:(2–6):(3–9). S2. Add the dispersant to the first part of water, add the F1 ultrafine water-control grade stone powder under stirring conditions of 1000-2000 r / min and disperse for 3-10 min, then perform surface occupancy treatment for 5-20 min, then add the amphoteric water-control polymer under stirring conditions of 300-600 r / min and stir for 2-5 min, and mature for 10-30 min to obtain F1 ultrafine water-control slurry; The amount of dispersant added, based on the effective solid mass of the dispersant corresponding to a unit mass of F1 ultrafine water-controlled stone powder, is 65% to 85% of the saturated adsorption capacity Qs of the F1 ultrafine water-controlled stone powder for the dispersant; the saturated adsorption capacity Qs is the adsorption plateau value determined after preparing a dispersion system of F1 ultrafine water-controlled stone powder and deionized water at a mass ratio of 1:1 at 24 to 26°C, adding the dispersant, and equilibrating for 30 min. S3. Add the manufactured sand, the F3 micro-aggregate grade stone powder and coarse aggregate into the mixer and dry mix for 20-40 seconds to distribute the F3 micro-aggregate grade stone powder between the manufactured sand particles. S4. Add cement, mineral admixtures and the F2 slurry filler stone powder, and dry mix for 15-30 seconds; S5. Add 65% to 85% of the total mixing water mass of the concrete and 70% to 90% of the total amount of the main polycarboxylate superplasticizer, and wet mix for 40 to 70 seconds to form a preliminarily dispersed main slurry of cement, mineral admixtures and F2 slurry filler stone powder. S6. Add the F1 ultrafine water-controlling slurry, the remaining mixing water and the remaining main polycarboxylate superplasticizer, and stir for 30-60 seconds to obtain the low-bleeding concrete; The water used to prepare the F1 ultrafine water-controlled slurry is included in the total mixing water of the concrete.
2. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 1, characterized in that, The F1 ultrafine water-controlled stone powder, F2 slurry-filled stone powder, and F3 micro-aggregate stone powder are obtained through dynamic air classification, cyclone classification, or wet classification. The particle size distribution overlap coefficients of F1 and F2, and F2 and F3, do not exceed 20%.
3. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 1, characterized in that, The proportion of particles with a diameter less than 2 μm in the F1 ultrafine water-controlled stone powder is no more than 40% of the mass of the F1 ultrafine water-controlled stone powder; the D50 of the F2 slurry-filled stone powder is 0.5 to 1.2 times the D50 of the cement used; and the D50 of the F3 micro-aggregate stone powder is 2.0 to 6.0 times the D50 of the cement used.
4. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 1, characterized in that, In each cubic meter of the low-bleeding concrete, the amount of F1 ultrafine water-controlling grade stone powder is 3-15 kg, the amount of F2 paste-filled grade stone powder is 15-50 kg, the amount of F3 micro-aggregate grade stone powder is 20-70 kg, and the total amount of the three is 45-120 kg; the dry weight ratio of F1 ultrafine water-controlling grade stone powder, F2 paste-filled grade stone powder and F3 micro-aggregate grade stone powder is 1:(3-5):(4-7).
5. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 1, characterized in that, Based on 100 parts by weight of the F1 ultrafine water-control grade stone powder, the F1 ultrafine water-control slurry comprises the following components: 100 parts by weight of F1 ultrafine water-control grade stone powder; 67-130 parts by weight of water; Dispersant: 0.10–0.80 parts by weight; Amphoteric water-controlling polymer, 0.005–0.10 parts by weight; Defoamer 0-0.10 parts by weight; The solid content of the F1 ultrafine water-controlled slurry is 43% to 60%.
6. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 5, characterized in that, The dispersant is selected from at least one of polyether phosphate and polycarboxylic acid dispersant; the carboxyl group density of the polycarboxylic acid dispersant is 0.40-0.50 mmol / g; the amphoteric water-controlling polymer is a water-soluble copolymer containing both anionic and cationic structural units, wherein the anionic structural unit includes a 2-acrylamido-2-methylpropanesulfonic acid structural unit, and the cationic structural unit includes a dimethyldiallylammonium chloride structural unit.
7. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 6, characterized in that, The relative weight-average molecular weight of the amphoteric water-controlling polymer is 200,000 to 2,000,000, and the cationic structural unit accounts for 5 to 20 mol% of all structural units of the amphoteric water-controlling polymer; based on 100 parts by mass of the F1 ultrafine water-controlling grade stone powder, the amount of the dispersant is 0.20 to 0.50 parts by mass, and the amount of the amphoteric water-controlling polymer is 0.015 to 0.060 parts by mass.
8. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 1, characterized in that, The saturated adsorption capacity Qs is determined according to the following method: At 24–26°C, different initial amounts of the dispersant were added to a dispersion system consisting of 50.00 g of F1 ultrafine water-controlled stone powder and 50.00 g of deionized water. The mixture was mixed and equilibrated for 30 min. The resulting dispersion system was subjected to solid-liquid separation, and the concentration of the dispersant in the supernatant was measured. The amount of unadsorbed dispersant was calculated based on the concentration of the dispersant in the equilibrium liquid phase and the total amount of liquid in the equilibrium system. The adsorption amount per unit mass of F1 ultrafine water-controlled stone powder was calculated based on the difference between the initial amount of dispersant added and the amount of unadsorbed dispersant. The adsorption amount corresponding to the plateau stage when the initial amount of dispersant added increased was determined as the saturated adsorption amount Qs.
9. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 1, characterized in that, The apparent viscosity of the F1 ultrafine water-controlled slurry at 25°C and a shear rate of 50 s⁻¹ is 50–500 mPa·s. After shearing at 500 s⁻¹ for 60 s, its apparent viscosity decreases by 30%–65% compared to before shearing. After stopping the 500 s⁻¹ shearing and allowing it to stand for 5 min, it is sheared at 50 s⁻¹ for 10 s, and the apparent viscosity at the 10th s is taken as the recovered apparent viscosity. The apparent viscosity recovery rate is the ratio of the recovered apparent viscosity to the apparent viscosity at the 60th s after shearing at 50 s⁻¹ for 60 s, and the apparent viscosity recovery rate is 35%–75%.
10. The preparation process of low-bleeding concrete using graded utilization of manufactured sand and gravel powder according to claim 1, characterized in that, Each cubic meter of the low-bleeding concrete comprises 240–380 kg of cement, 30–100 kg of fly ash, 30–120 kg of mineral powder, 3–15 kg of F1 ultrafine water-controlling grade stone powder, 15–50 kg of F2 slurry-filling grade stone powder, 20–70 kg of F3 micro-aggregate grade stone powder, 650–900 kg of manufactured sand, 900–1150 kg of coarse aggregate, 140–175 kg of water, and 3–10 kg of polycarboxylate admixture. In the combined fine aggregate composed of manufactured sand and F3 micro-aggregate grade stone powder, particles with a diameter of 0.075 to 0.15 mm account for 3.0% to 6.5% of the mass of the combined fine aggregate, and the fineness modulus of the combined fine aggregate is 2.5 to 3.1.
Citation Information
Patent Citations
Method for improving gradation of machined sand
CN103113033B
Low-bleeding-rate concrete based on low-stone-powder-content machine-made sand and preparation method of low-bleeding-rate concrete
CN117447142A
